2010
DOI: 10.1519/jsc.0b013e3181e2e081
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Short-Term Combined Conditioning Training for the Development of Leg Strength and Power

Abstract: The aim of the study was to compare the effect of combined weight and pendulum training exercises with those isolated ones on muscle strength and vertical jump performance. A total of 38 young active men were divided into 4 groups performing different combinations of strength and power training and measured directly and 2 weeks after the training program. Weight training and pendulum swing exercises, involving lower body during dynamic bounces, were used. Results of 1 repetition maximum (1RM) in full squat and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Core training is rarely performed as an isolated training modality, but rather as part of a larger overall fitness routine. Therefore, it is not surprising that seven studies [9][10][11]18,20,26,27] reported significant improvements in maximum lift performance during post-testing. Likewise, it seems intuitive that interventions that targeted the core would show improvements in measures of core stability and endurance.…”
Section: General Performancementioning
confidence: 99%
“…Core training is rarely performed as an isolated training modality, but rather as part of a larger overall fitness routine. Therefore, it is not surprising that seven studies [9][10][11]18,20,26,27] reported significant improvements in maximum lift performance during post-testing. Likewise, it seems intuitive that interventions that targeted the core would show improvements in measures of core stability and endurance.…”
Section: General Performancementioning
confidence: 99%
“…This result means that female nondance and dance majors have similar muscular strength, which might limit the ability of the latter to perform active and accurate movements such as standing, locomotion, or dynamic jumping or turning. Thus, it was reported that plyometric training would be proper for dance major students to efficiently improve quadriceps femoris strength, which is critical to dance performance ( Sáez-Sáez de Villarreal et al, 2010 ; Trzaskoma et al, 2010 ). It is also important that they maintain balanced muscle strength of the biceps femoris, which plays an important role as a flexor in the lower limbs, and resistance exercises such as leg curls are required to improve flexor strength.…”
Section: Discussionmentioning
confidence: 99%
“…Core training is rarely performed as an isolated training modality, but rather as part of a larger overall fitness routine. Therefore, it is not surprising that seven studies [911,18,20,26,27] reported significant improvements in maximum lift performance during post-testing. Likewise, it seems intuitive that interventions that targeted the core would show improvements in measures of core stability and endurance.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Similarly, Trzaskoma and associates saw increases in 1-RM squat and hip and knee flexor and extensor strength following a 2-week protocol that included four different combinations or traditional weight ‘training and pendulum swim exercises. [27] O’Bryant and colleagues compared a ‘periodized’ (high volume, low intensity) training programme with traditional weight training, both of which included aspects of core training. [26] Both training modalities increased maximum strength and endurance on cycle ergometer testing, while the periodized group produced superior results.…”
Section: Discussionmentioning
confidence: 99%